Chemical composition of forage watermelon fruit at different maturity stage or storage length - Alessandra Bezerra de Azeredo; Ana Paula Ribeiro da Silva; Alex Gomes da Silva Matias; Valterlina Moreira da Silva; Airton Alves Vieira Correia; Tadeu Vinhas Voltolini (Acta Scientiarum. Animal Sciences, 2021)
This study aimed to assess the chemical responses of forage watermelon fruit at different maturity stages or storage lengths, performing two experimental tests. In the first test, four maturity stages were assessed: 30, 45, 60, and 75 days after anthesis, with four replicates. In the second test, fruits were maintained under three storage lengths: T1D (harvest day), T3M (3 months after harvest), and T6M (6 months after harvest), with eight replicates. Experimental design was completely randomized in both experimental tests. Fruit maturity stage did not affect crude protein, total carbohydrate, neutral detergent fiber, in vitro dry matter digestibility (IVDMD), pulp firmness, soluble solids content and total pectin content, but increased acid detergent fiber content from 45 days after anthesis. Storage length up to six months after harvest increased ash, crude protein and IVDMD, and reduced the content of soluble solids. Forage watermelon fruit can be harvested from 30 to 75 days after anthesis equivalent to 75 - 120 days after planting, and they can be stored under tree shade up to 6 months after harvest.